PEMODELAN DAN SIMULASI DISTRIBUSI KAOS CUSTOM DENGAN ANYLOGIC (STUDI KASUS KONVEKSI KAOS SURABAYA) - M Saifudin Azizi; Yoga Aditiatama; Moh Khusnul Mubarak; Dwi Rolliawati (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2020)
Business activities that function in the discipline of convection are very dependent on the production technique carried out. Effectiveness and effectivity want to be viewed in using human resources and also management factors. Surabaya T-shirt convection has many customers in more than a few regions in Surabaya, but still can't maximize its distribution strategy. By the use of distribution simulations it is hoped that it can improve the first-rate of Surabaya T-shirt convection administration in managing the ups and downs of patron demand, the exceptional of the service of Surabaya T-shirt convection increases. Especially in shipping by the distributor. By including units according to the variety of retails, the accuracy of distribution can reach 100%.